Third-wave interventions for eating disorders in adolescence – systematic review with meta-analysis - Arne Buerger; Timo D. Vloet; Lisa Haber; Julia M. Geissler (Borderline Personality Disorder and Emotion Dysregulation, 2021)
Abstract Context Third-wave therapies have demonstrated efficacy as a treatment option for EDs in adulthood. Data on the suitability for EDs in adolescence are lacking. Objective To estimate the efficacy of third-wave interventions to reduce ED symptoms in adolescents in randomized controlled trials (RCTs) and uncontrolled studies. Data sources We systematically reviewed the databases PubMed (1976-January 2021), PsycINFO (1943-January 2021), and the Cochrane database (1995-January 2021) for English-language articles on third-wave therapies. References were screened for further publications of interest. Study selection RCTs and pre-post studies without control group, comprising patients aged 11–21 years (mean age = 15.6 years) with an ED diagnosis (anorexia nervosa, bulimia nervosa, binge eating disorder, eating disorder not otherwise specified) investigating the efficacy of third-wave psychological interventions were included. Efficacy had to be evaluated according to the Eating Disorder Examination or Eating Disorder Examination-Questionnaire, the Eating Disorder Inventory-2, the Eating Disorder Inventory-3, or the Structured Interview for Anorexic and Bulimic Disorders for DSM-IV and ICD-10. The outcome assessed in the meta-analysis was the EDE total score. Data extraction Independent extraction of data by two authors according to a pre-specified data extraction sheet and quality indicators. Data synthesis We identified 1000 studies after removal of duplicates, assessed the full texts of 48 articles for eligibility, and included 12 studies with a total of 487 participants (female 97.3%/male 2.6%) in the qualitative synthesis and seven studies in the meta-analysis. Articles predominantly reported uncontrolled pre-post trials of low quality, with only two published RCTs. Treatments focused strongly on dialectical behaviour therapy (n = 11). We found moderate effects of third-wave therapies on EDE total score interview/questionnaire for all EDs (d = − 0.67; z = − 5.53; CI95% = − 0.83 to − 0.59). Descriptively, the effects appeared to be stronger in patients with BN and BED. Conclusion At this stage, it is not feasible to draw conclusions regarding the efficacy of third-wave interventions for the treatment of EDs in adolescence due to the low quality of the empirical evidence. Since almost all of the identified studies used DBT, it is unfortunately not possible to assess other third-wave treatments’ efficacy.